Influence of the thermal сonditions within the bed of the last ice sheet on the distribution of glacial valleys of the Belarusian Poozerie area - Komarovskiy, Michail E.; Khilkevich, Ekaterina V. (Journal of the Belarusian State University. Geography and Geology, 2022)
Within the bed of the Poozerie (Weichselian) ice sheet, which occupied the northern part of Belarus at the maximum stage and at the beginning of degradation, three concentric thermal zones were identified according to geological and geomorphological criteria: the outer zone of basal frozen ice, the zone of discontinuous frozen bed, the inner zone of the thawed bed. Comparison of glacial valleys with thermal zoning shows that their distribution and formation closely related to thermal conditions. During the Poozerie (Weichselian) ice sheet advance into the northern region of Belarus, thermal zoning affected geological denudation processes. This led to local erosion and valleys in the outer zone of basal frozen ice, large-scale manifestation of glacial excavation and squeesing out and the formation of lobate glacial depressions, large radial valleys and subglacial lakes in the inner zone of the thawed bed and along its outer border with the zone of discontinuous frozen bed. The formation of large tunnel valleys became possible at the stage of degradation of the ice sheet (Vitebsk phase), after the melted glacial waters of subglacial dammed lakes found an outlet into the marginal zone through an intermittent frozen bed and were released as a result of catastrophic floods through separate channels, which were deepened, widened and formed tunnel valleys.
Keywords: glacial valleys; marginal zone; basal thermal conditions; thawed ice bed; frozen ice bed; the last ice sheet